2013
DOI: 10.1590/s2176-94512013000100015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of saliva contamination on bond strength witha hydrophilic composite resin

Abstract: How to cite this article: Deprá MB, Almeida JX, Cunha TMA, Lon LFS, Retamoso LB, Tanaka OM. Effect of saliva contamination on bond strength with a hydrophilic composite resin. Dental Press J Orthod. 2013 Jan-Feb;18(1):63-8. » The author reports no commercial, proprietary or financial interest in the products or companies described in this article. Objective: To evaluate the influence of saliva contamination on the bond strength of metallic brackets bonded to enamel with hydrophilic resin composite. Methods: Ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
(19 reference statements)
0
5
0
4
Order By: Relevance
“…This result was in line with those of Cacciafesta et al 9,23 . On the other hand, the results of Prasad et al 10 , Santosa et al 11 , Cacciafesta et al 23 and Deprá 24 presented significant reduction in the bond strength of conventional adhesive types when subjected to saliva contamination during the bonding procedures. This was attributed to the hydrophobic nature of the conventional adhesives.…”
Section: Discussionmentioning
confidence: 93%
“…This result was in line with those of Cacciafesta et al 9,23 . On the other hand, the results of Prasad et al 10 , Santosa et al 11 , Cacciafesta et al 23 and Deprá 24 presented significant reduction in the bond strength of conventional adhesive types when subjected to saliva contamination during the bonding procedures. This was attributed to the hydrophobic nature of the conventional adhesives.…”
Section: Discussionmentioning
confidence: 93%
“…The conventional composite used the Transbond XT, which is the orthodontic light-curing resin, considered the "gold standard" of adhesive resistance [7,9,13,14,24,25]. The hydrophilic composite Transbond Plus Color Change is a light-curing adhesive system that, according to the manufacturer, provides reliable, protective, and moisturetolerant bonding.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that contamination by saliva or blood decreases the shear strength of brackets or tubes bonded with the conventional hydrophobic composite Transbond XT [8,9,24]. The use of the hydrophilic composite Transbond Plus Color Change associated with the Self Etching Primer, in an environment contaminated by saliva, provided adequate adhesive resistance for clinical use [14].…”
Section: Discussionmentioning
confidence: 99%
“…Visando melhorar a colagem de braquetes e acessórios ortodônticos em meio úmido, a indústria odontológica vem desenvolvendo novos adesivos hidrofílicos para que, além de diminuírem os passos clínicos na rotina profissional, sejam resistentes às forças ortodônticas e de mastigação 19 . Estes resultados concordam com outros estudos [16][17][18]21 , comprovando que estes materiais apresentam adequada performance, mesmo quando há contaminação. Estes resultados proporcionam segurança ao clínico, já que o ambiente bucal é extremamente úmido e, mesmo com cuidados de controle da saliva, pode ocorrer esta contaminação durante o procedimento de colagem de braquetes.…”
Section: Discussionunclassified